Who is Andesiops peruvianus (Ulmer, 1920) (Ephemeroptera: Baetidae)? New insight from the type basin using morphological and molecular analyses - Mera, Renzo; Siccha-Ramirez, Raquel; Ramirez, Jorge L.; Núñez-Rodríguez, Daniela; Britzke, Ricardo; Velásquez-Rodríguez, Karen; Ramírez, Rina; Huamantinco, Ana A. (Zootaxa, 2023)
Andesiops peruvianus (Ulmer, 1920) is a small minnow mayfly with a distribution throughout the Andes Mountains, mainly in lotic environments. In recent years, the taxonomic status of the species has been shifting, even finding out molecular and morphological evidence to consider it as a cryptic species. In this work, we collected seven specimens of A. peruvianus from the Lake Titicaca in Peru, the type locality and perform molecular and morphological analyses to test their relationship with specimens from other regions. The species delimitation analysis revealed the existence of five MOTUs for specimens identified as A. peruvianus along the Andes Mountains, while the Lake Titicaca specimens formed a single MOTU with high interspecific distance. In this MOTU were found specimens with different types of abdominal gills, from translucent to markedly tracheated supporting the hypothesis of phenotypic plasticity at the abdominal gill level. Also, an extension in the range of tarsal claw denticles, from 10–12 to 10–14, were observed, higher than what were found in other regions. Our results support A. peruvianus as a species complex and reveal A. peruvianus from Titicaca as a single MOTU. Future morphological revisions of topotype specimens as well as from other Andean regions are required to strengthen the diagnosis of informative characteristics at both the larval and adult stage to elucidate the real status of the species.